2020
DOI: 10.1126/sciadv.abd1160
|View full text |Cite
|
Sign up to set email alerts
|

Two phenotypically and functionally distinct microglial populations in adult zebrafish

Abstract: Microglia are the tissue-resident macrophages in the central nervous system and are critically involved in immune defense, neural development and function, and neuroinflammation. The versatility of microglia has long been attributed to heterogeneity. Recent studies have revealed possible heterogeneity in human but not in murine microglia, yet a firm demonstration linking microglial heterogeneity to functional phenotypes remains scarce. Here, we identified two distinct microglial populations in adult zebrafish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 66 publications
5
74
0
Order By: Relevance
“…In contrast, the positive role of microglia in zebrafish telencephalic regeneration has been recently highlighted [ 96 , 172 ]. Importantly, in contrast to mammalian microglia cells, for which recent transcriptomic analysis have shown a relative homogeneity during adulthood, zebrafish microglia can be separated into two subpopulations (ccl34b positive and negative) displaying different phenotypes and functions [ 95 ]. Wu et al raised the question of the functional specialization of microglial in fish linked to multiple rounds of genomic duplication [ 183 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the positive role of microglia in zebrafish telencephalic regeneration has been recently highlighted [ 96 , 172 ]. Importantly, in contrast to mammalian microglia cells, for which recent transcriptomic analysis have shown a relative homogeneity during adulthood, zebrafish microglia can be separated into two subpopulations (ccl34b positive and negative) displaying different phenotypes and functions [ 95 ]. Wu et al raised the question of the functional specialization of microglial in fish linked to multiple rounds of genomic duplication [ 183 ].…”
Section: Resultsmentioning
confidence: 99%
“…In zebrafish, two microglial populations have been documented, differing in morphology, distribution, and functions [ 95 ]. The main population corresponds to phagocytotic microglia (ccl34b.1-positive) and is widely distributed, highly mobile, and phagocytic.…”
Section: Cellular Events Occurring After Telencephalic Injury In Zmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-cell transcriptomic studies have revealed signatures of neurodegenerative disease-associated microglia (DAM) (35,36) and bulk RNA studies have delineated regeneration-associated microglia (RAM; (37)). That functionally discrete microglia subtypes exist was recently confirmed in a mouse model of retinal degeneration (38) and in zebrafish brain (39). AO-LLSM imaging data suggests an extension of this concept, with functional divergence arising even among neighboring microglia.…”
Section: Discussionmentioning
confidence: 82%
“…However, this heterogeneity pales when compared to the heterogeneity in humans ( Geirsdottir et al, 2020 ). Furthermore, microglial heterogeneity is recognized in zebrafish ( Wu et al, 2020 ). However, the extent to which these heterogenous microglial populations are already present in ancestral species remains to be adequately clarified.…”
Section: Conclusion and Outstanding Questionsmentioning
confidence: 99%